Material for high-metal-phase metal ceramic inert anode as well as preparation method and application of material

Through the combination of high metal phase and ceramic phase and vacuum hot pressing sintering process, high metal phase metal cermet inert anode material with good conductivity, thermal shock resistance and corrosion resistance is prepared, which solves the problems of complex material preparation and poor performance matching, and is suitable for large-scale industrial production.

CN119736542APending Publication Date: 2025-04-01ZHENGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411753734.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

There are few researches on materials for inert anodes of high metal phase metal cermets, complex preparation methods, poor matching of corrosion resistance, thermal shock resistance and mechanical processing properties of the materials, resulting in small anode size and low fault tolerance, making it difficult to adapt to large-scale industrial production.

Method used

The materials composed of high metal phases (Ni, Fe, Cu) and ceramic phases (NiFe2O4-based ceramics) are prepared by vacuum hot pressing sintering process to control the Ni and Fe ratios of the metal phase and the NiO content of the ceramic phase to form a dense passivation layer to improve the corrosion resistance and conductivity of the material.

Benefits of technology

It has achieved good conductivity, thermal shock resistance, corrosion resistance and mechanical processing of high-metal phase cermet inert anode materials, and is suitable for large-scale production and industrial-grade applications, improving the service life and fault tolerance of the anode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736542A_ABST
    Figure CN119736542A_ABST
Patent Text Reader

Abstract

The invention discloses a material for a high-metal-phase metal ceramic inert anode and a preparation method and application thereof, belongs to the technical field of aluminum electrolysis, and solves one of the problems that in the prior art, a preparation method of a material for a metal-phase metal ceramic inert anode is complex, and the matching performance of corrosion resistance, thermal shock resistance and machinability of the material is poor. The material for the high-metal-phase metal ceramic inert anode is composed of a metal phase and a ceramic phase. By mass fraction, the metal phase accounts for 51-99% of the material for the high-metal-phase metal ceramic inert anode, and the rest is the ceramic phase; the metal phase comprises Ni, Fe and Cu, and in the metal phase, the mass fraction of Ni is 30%-60%. The material for the high-metal-phase metal ceramic inert anode has good electrical conductivity, thermal shock resistance, corrosion resistance and machinability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum electrolysis, and in particular to a high-metal phase metal ceramic inert anode material and a preparation method and application thereof. Background Art

[0002] Aluminum electrolysis, one of the key emission reduction industries in non-ferrous metal smelting, is facing tremendous pressure. Carbon emissions in the aluminum electrolysis process mainly occur in the oxidation of carbon anodes. The oxygen ions produced by the decomposition of Al2O3 in the molten electrolyte under the action of the electric field combine with carbon to release CO2 gas. In more extreme cases, carbon tetrafluoride will be produced. To eliminate this phenomenon, the use of inert anodes has become a key technical direction for zero-carbon aluminum electrolysis.

[0003] The earliest inert anode was the precious metal Pt, but it could not be used in large quantities due to its high price; a variety of single metals such as alkali metals Cu, Fe, Ni, Cr, etc. were selected, but they could not be used due to severe corrosion. Sadway cleverly used the different physical and chemical properties of each metal to match the alloy anode to a certain extent, which improved the corrosion resistance and was easy to process and could be large-scale, but it still did not solve the corrosion problem of the alloy. It failed due to the low purity of the product aluminum caused by its high corrosion. On the other hand, the conductive oxide ceramic NiFe2O4 is favored for its good corrosion resistance, but its excessive processing difficulty makes it difficult to use. The composite of metal and ceramic is cermet, which can take into account the high conductivity, machinability of metal and corrosion resistance of oxide ceramic. It is another major advancement in inert anode technology, but the high ceramic phase sacrifices its conductivity, thermal shock resistance and processing performance when improving the corrosion resistance of the material. Cermet is difficult to adapt to large-scale industrial production.

[0004] From the development history of inert anodes, it can be seen that the corrosion resistance of materials has always been the focus of the industry. At present, the industrial application of inert anodes by major companies is also full of difficulties. The reason is that the structure of the traditional aluminum electrolytic cell causes the anode, molten electrolyte, and electrolysis products to be in the same cell body, and the impurity elements of the anode material are easy to enter the aluminum liquid and cannot meet the product requirements. To address this problem, based on the new structure mediated by liquid metal, the medium between the two chambers separates the inert anode and the product, and impurity elements are difficult to enter the product to achieve the purification of the aluminum liquid. Therefore, the performance selection of metal ceramic materials is no longer limited to extremely high corrosion resistance, and high metal phase metal ceramics also have application prospects. There is currently little research on high metal phase metal ceramic inert anodes, and the matching of corrosion resistance and processability of high metal phase metal ceramic inert anodes has not been deeply studied. In addition, the existing preparation method of metal phase metal ceramic inert anodes is relatively complicated and the production cost is high. Summary of the invention

[0005] In view of the above situation, the present invention aims to provide a material for a high metallic phase metal ceramic inert anode and a preparation method and application thereof, so as to solve one of the following technical problems: there is little research on materials for a high metallic phase metal ceramic inert anode, the preparation method of materials for a metal phase metal ceramic inert anode is complicated, the matching of the corrosion resistance, thermal shock resistance and machinability of the materials is poor, and currently the metal ceramic inert anode is restricted by the material properties, the size is small, and multiple groups of anodes are often used together, and the fault tolerance rate is low.

[0006] The purpose of the present invention is mainly achieved through the following technical solutions:

[0007] The present invention provides a high-metallic phase metal ceramic inert anode material, which consists of a metal phase and a ceramic phase; in terms of mass fraction, the metal phase accounts for 51% to 99% of the high-metallic phase metal ceramic inert anode material, and the rest is the ceramic phase; the metal phase contains Ni, Fe, and Cu, and the mass fraction of Ni in the metal phase is 30% to 60%.

[0008] Furthermore, the ceramic phase is NiFe2O4-based ceramic.

[0009] Furthermore, in the metal phase, the molar ratio of Ni to Fe is 1.5:2 to 3:2.

[0010] Furthermore, the ceramic phase also includes NiO.

[0011] The present invention also provides a method for preparing the above-mentioned high metallic phase metal ceramic inert anode material, comprising the following steps:

[0012] Step 1, pre-drying the metal powder and the oxide powder respectively;

[0013] Step 2, mixing the metal powder and the oxide powder after drying and pretreatment, adding a dispersant, and ball milling to obtain a slurry;

[0014] Step 3, drying the slurry;

[0015] Step 4: vacuum hot-pressing and sintering the dried powder to obtain a high-metallic phase metal ceramic inert anode material.

[0016] Furthermore, in step 1, the metal powder includes Ni powder, Fe powder and Cu powder, and the oxide powder includes NiO and Fe2O3.

[0017] Furthermore, in step 2, the dispersant is anhydrous ethanol.

[0018] Furthermore, in step 2, the mass ratio of the dispersant to the sum of the mass of the metal powder and the oxide powder is 2 to 4:5.

[0019] Furthermore, in step 3, the drying temperature is 85-110°C.

[0020] Furthermore, in step 4, the sintering temperature is 1000-1180°C.

[0021] The present invention also provides an application of a high-metal phase metal ceramic inert anode material. The high-metal phase metal ceramic inert anode material can be used for an inert anode.

[0022] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0023] a) The high metallic phase metal ceramic inert anode material of the present invention has a higher metallic phase, making the high metallic phase metal ceramic inert anode material more metallic, and by precisely controlling the ratio of Ni and Fe in the metal phase, the appropriate ratio of Ni and Fe in the metal phase in a molten salt environment will promote the formation of NiFe2O4, which can form a dense passivation layer in cooperation with the ceramic phase, thereby ensuring the corrosion resistance of the material. The high metallic phase metal ceramic inert anode material of the present invention has good electrical conductivity, thermal shock resistance, corrosion resistance, and machinability.

[0024] b) In the preparation method of the high metallic phase metal ceramic inert anode material of the present invention, the type and content of the raw materials used are precisely controlled, and combined with the process steps and process parameters, vacuum hot pressing and sintering are used to obtain the high metallic phase metal ceramic inert anode material with excellent performance. The method is simple and suitable for industrial production.

[0025] c) The method used in the present invention omits the synthesis step of NiFe2O4, directly mixes NiO and Fe2O3 with metal powder, performs vacuum hot pressing sintering, and prepares the metal ceramic material in one step, thereby shortening the preparation process of the inert anode. At the same time, the high metal phase metal ceramic inert anode material of the present invention is easy to realize large-scale production of the material.

[0026] d) The high metallic phase metal ceramic inert anode material of the present invention has good electrical conductivity, thermal shock resistance, corrosion resistance, and machinability, can be used for metal ceramic inert anodes, and can promote the large-scale development and industrial-grade application of metal ceramic inert anodes.

[0027] Other features and advantages of the present invention will be described in the following description, and part of them will become obvious from the description, or will be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the contents particularly pointed out in the written description and the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0029] Figure 1 The microstructure morphology of the high metallic phase metal ceramic inert anode material of Example 1;

[0030] Figure 2 The microstructure morphology of the high metallic phase metal ceramic inert anode material of Example 4;

[0031] Figure 3 This is the microstructure morphology of the high metallic phase metal ceramic inert anode material of Example 5. DETAILED DESCRIPTION

[0032] Preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used to explain the principles of the present invention together with the embodiments of the present invention.

[0033] The present invention provides a high metallic phase metal ceramic inert anode material, which consists of a metal phase and a ceramic phase; in terms of mass fraction, the metal phase accounts for 51% to 99% of the high metallic phase metal ceramic inert anode material, for example, 55%, 60%, 70%, 75%, 80%, 85%, 90%, 95%, and the rest is a ceramic phase; the metal phase contains Ni, Fe, and Cu, and the mass fraction of Ni in the metal phase is 30% to 60%, for example, 40%, 45%, 50%, 55%; the ceramic phase is a NiFe2O4-based ceramic.

[0034] Specifically, in the above metal phase, the content of Fe is related to the content of Ni, wherein the molar ratio of Ni to Fe is 1.5:2 to 3:2; the remainder is Cu.

[0035] It should be noted that in the high metallic phase metal ceramic inert anode material of the present invention, the metal phase is mainly composed of nickel, which makes the material have better corrosion resistance in high-temperature molten salt and can increase the service life; at the same time, Fe and Ni are added to combine with each other to form an oxide layer, and Cu is added to improve the conductivity of the material.

[0036] It should be noted that in the metal phase, the mass fraction of Ni is better when it is above 30%. At this time, the Ni on the surface of the material can form an oxide film to protect the base metal; if Ni is less than 30%, the content of Fe and Cu is too high. These two elements are easy to combine with O and F in the high-temperature molten electrolyte, causing the anode surface material to peel off, thereby continuously exposing new base surfaces and aggravating the corrosion of the anode. The upper limit of Ni content is also affected by the molar ratio of nickel and iron. In the extreme case, Cu is not contained, and the molar ratio of nickel and iron takes the maximum value of 3:2, at which time its upper limit is 61.25%.

[0037] It should be noted that the nickel-iron molar ratio of the present invention is based on the need to obtain a NiFe2O4 oxide layer. In the process of electrolyzing molten alumina using an inert anode, oxygen will be released, and Ni and Fe will react with oxygen, so selecting an appropriate nickel-iron ratio can effectively generate this oxide layer. Theoretically, according to the NiFe2O4 nickel-iron molar ratio, 1:2 can be selected, but the inventors found in the study that Fe in the electrolysis process has a tendency to move to the anode surface and be corroded and dissolved by molten salt. Therefore, selecting an excessive amount of nickel can hinder the loss of iron and create time for the formation of a dense oxide layer NiFe2O4; when the nickel-iron molar ratio is too large, the Ni content in the material will be too high and enrichment will be unfavorable for the combination of Ni and Fe, and the oxide layer will be difficult to achieve density. On the other hand, nickel oxide is not a conductive material. After high-temperature oxidation, the conductivity of the material will be reduced, which is not conducive to the stable operation of electrolysis. Therefore, the molar ratio of Ni to Fe is controlled at 1.5:2 to 3:2. In terms of mass fraction, only with respect to nickel and iron, the mass ratio of Ni to Fe is 0.78 to 1.58, and preferably, the mass ratio of Ni to Fe is 1.15 to 1.56.

[0038] Specifically, the above ceramic phase is NiFe2O4-based oxide ceramic.

[0039] Preferably, the ceramic phase may further include NiO, and the content of NiO ceramic phase in the ceramic phase is ≤35% by mass.

[0040] Specifically, NiO is doped into the metal ceramic inert anode material, and its effects are as follows: it can weaken or inhibit the occurrence of certain chemical reactions, such as the fluorination of nickel and the oxidation of copper. The inventors have conducted in-depth research and found that the addition of NiO can reduce the decomposition voltage of aluminum oxide and the oxygen evolution potential, which is beneficial to the occurrence of the reaction; on the other hand, NiO will further react with NiFe2O4 during the sintering process in a weak oxygen environment, and the newly generated substance has good conductivity, which is beneficial to electrolysis operation.

[0041] The present invention also provides a method for preparing the above-mentioned high metallic phase metal ceramic inert anode material, comprising the following steps:

[0042] Step 1, pre-drying the metal powder and the oxide powder respectively;

[0043] Step 2, mixing the metal powder and the oxide powder after drying and pretreatment, adding a dispersant, and ball milling to obtain a slurry;

[0044] Step 3, drying the slurry, and the dried powder is a uniform mixture of metal powder and ceramic powder;

[0045] Step 4: vacuum hot-pressing and sintering the powder to obtain a high-metallic phase metal ceramic inert anode material.

[0046] Specifically, in the above step 1, the metal powder includes Ni powder, Fe powder and Cu powder, and the oxide powder includes NiO and Fe2O3.

[0047] Specifically, in the above step 1, the metal powder and the oxide powder are both analytically pure powders, and considering that the larger the particle size of the powder, the smaller the contact area of ​​the raw material powder, which is not conducive to the subsequent solid phase reaction in the later preparation process, the powder is sieved through a -100 mesh screen.

[0048] Specifically, in the above step 1, the purpose of the drying pretreatment is to remove the adsorbed moisture and some impurities. In order to avoid oxidation of the metal powder during the drying pretreatment, the metal powder is dried by vacuum drying or atmosphere drying; for example, the temperature of the metal powder drying pretreatment is 75-100°C, such as 80°C, 85°C, 90°C, 95°C, and the time is 8-16h, such as 9h, 10h, 11h, 12h, 13h, 14h, 15h; the temperature of the oxide powder drying pretreatment is 85-120°C, such as 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, and the time is 12-24h, such as 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h.

[0049] Specifically, in the above step 2, the dispersant is anhydrous ethanol.

[0050] Considering that the functions of the dispersant are to prevent the powders from rubbing against each other and causing a reaction, and to prevent the air from contacting too much with the metal powders to prevent oxidation; the amount of the dispersant is related to the amount of the powder raw materials, too little dispersant will not play a role in dispersion and isolation, and the dispersant should immerse the raw material powders; but in the ball milling process, too much dispersant increases the raw material loss rate. Therefore, the mass ratio of the dispersant to the sum of the mass of the metal powder and the oxide powder is controlled to be 2 to 4:5.

[0051] Specifically, in the above step 2, the purpose of ball milling is uniform mixing and powder grinding. The ball milling speed and time are determined according to the state of the raw materials. A faster speed can be selected for fine powder to achieve the purpose of uniform mixing, and a slower speed should be selected for coarse powder to obtain greater friction to grind the powder, and the ball milling time should also be extended. In step 2, the finer the mixed powder in the final slurry, the better, and the mixed powder in the slurry is controlled to be less than 325 mesh.

[0052] Specifically, in the above step 2, the ball milling speed is 300-500 rpm, for example 350 rpm, 400 rpm, 450 rpm, and the ball milling time is 6-18 h, for example 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h.

[0053] Specifically, in the above step 3, the purpose of drying is to dry the anhydrous ethanol in the slurry to obtain a uniformly mixed powder. The drying temperature is controlled to be 85-110°C, such as 90°C, 95°C, 100°C, 105°C, and the drying time is 12-24h, such as 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h.

[0054] Specifically, in the above step 3, the drying method is preferably vacuum drying. Because of the existence of steam pressure, a longer drying time should be selected.

[0055] Specifically, in the above step 4, the vacuum hot pressing sintering step includes: placing the powder mold in a furnace, reducing the vacuum degree to less than 1 Pa, heating and pressurizing to the sintering temperature, maintaining the temperature and pressure, and demolding to obtain a high metallic phase metal ceramic inert anode material.

[0056] Specifically, in the above step 4, considering that the purpose of vacuum hot pressing sintering is to obtain a high metal phase metal ceramic inert anode material, the key step is the reaction of NiO and Fe2O3 to synthesize NiFe2O4. This reaction is an exothermic reaction and requires heating to provide the power for the reaction. Considering that too high a temperature will lead to forming failure, the sintering temperature is controlled to be 1000-1180°C, such as 1030°C, 1050°C, 1080°C, 1100°C, 1130°C, 1150°C, and the holding time is 1-3h.

[0057] Specifically, in the above step 4, the pressurization during the sintering process is to obtain a higher material density, which affects the service life of the inert anode. Low-density materials have many voids, and the molten electrolyte will corrode the inside of the material along the voids, which can easily cause the material surface to peel off, and in severe cases, it will cause the material to rupture or even disintegrate. Therefore, in order to ensure the density of the material, the sintering pressure is controlled to 20-35MPa, such as 25MPa, 28MPa, and 30MPa.

[0058] Specifically, in the above step 4, the vacuum hot pressing sintering step includes: placing the powder mold in a furnace, reducing the vacuum degree to less than 1Pa, heating to 550-600°C, and keeping warm for 0.5-2h; continuing to heat and pressurize to the sintering temperature, keeping warm and pressurizing, and demolding to obtain a high metallic phase metal ceramic inert anode material.

[0059] Heating to 550-600°C and keeping it warm for 0.5-2h can further remove any residual moisture and organic matter in the powder.

[0060] Specifically, in the above step 4, if the cooling rate is too fast, the internal thermal stress of the material cannot be fully released, and cracking may occur during preparation and use; if the cooling rate is too slow, the material will be kept in a high temperature environment for a long time, and the grains will repolymerize and grow, resulting in a decrease in the physical properties of the material. Therefore, after controlling the heat preservation and pressure, the temperature is reduced to room temperature at a rate of 4-7℃ / min for demoulding.

[0061] The high metal phase metal ceramic inert anode material of the present invention has high density, good electrical conductivity, thermal shock resistance, corrosion resistance (equivalent annual corrosion rate is less than 1.45 cm / a), and machinability, and can be used for metal ceramic inert anode. For example, the density is more than 94% (for example, 94% to 98%), the room temperature electrical conductivity is more than 3424.66 S / cm (for example, 3424 to 2.5×10 4 S / cm), and further, the high metallic phase metal ceramic material can be used for the preparation of large-size materials, for example, it can be used to prepare materials larger than Φ30 mm, such as Φ(30-100) mm×(10-200) mm, or can be used to prepare block materials, such as (50-300) mm×(30-200) mm×(10-200) mm, which can be large-scaled and is conducive to the industrial production of inert anodes.

[0062] The technical solution of the present invention is further explained below in conjunction with specific embodiments.

[0063] It should be noted that the material performance testing method is:

[0064] Density: The apparent density of the material is determined by the Archimedes drainage method. The density is the ratio of the actual density to the theoretical density.

[0065] Thermal shock resistance: The prepared material is subjected to a rapid heating and cooling cycle test. The material is directly placed in a muffle furnace at 780°C to rapidly heat it up. After 30 minutes, it is taken out and quickly cooled in water, completing a thermal shock. This process is repeated until cracks or damage appear on the sample. The more thermal shock cycles, the better the thermal shock resistance of the material.

[0066] Conductivity: At room temperature, the resistivity of the material is tested using a four-probe detector and the conductivity is calculated.

[0067] Electrolysis experiment: The electrolysis experiment was carried out using a double-chamber structure electrolytic furnace and maintained for more than 12 hours. The average cell pressure during the aluminum electrolysis process was taken as the average working voltage of the anode.

[0068] Example 1

[0069] This embodiment provides a high-metallic phase metal ceramic inert anode material, which is composed of a metal phase and a ceramic phase;

[0070] In the material for high metallic phase cermet inert anode, the metal phase accounts for 75% by mass, and the rest is ceramic phase;

[0071] The metal phase contains Ni, Fe and Cu. In terms of mass fraction, the mass fraction of Ni is 43%, the mass fraction of Fe is 32% and the mass fraction of Cu is 25%. The ceramic phase is NiFe2O4-based ceramic.

[0072] The preparation method of the high metallic phase metal ceramic inert anode material of the present embodiment comprises the following steps:

[0073] Step 1, pre-drying the metal powder and the oxide powder respectively;

[0074] Step 2, mixing the metal powder and the oxide powder after drying and pretreatment, adding anhydrous ethanol, and ball milling to obtain a slurry;

[0075] Step 3, drying the slurry, and the dried powder is a uniform mixture of metal powder and ceramic powder;

[0076] Step 4: vacuum hot-pressing and sintering the powder to obtain a high-metallic phase metal ceramic inert anode material.

[0077] Specifically, in the above step 1, the metal powder includes Ni powder, Fe powder and Cu powder, and the oxide powder includes NiO and Fe2O3; the mass ratio of the metal powder to the oxide powder is 75:25; in the metal powder, the mass fraction of Ni is 43%, the mass fraction of Fe is 32%, and the mass fraction of Cu is 25%; in the oxide powder, the mass fraction of NiO is 31.92%, and the mass fraction of Fe2O3 is 68.08%.

[0078] Specifically, in the above step 1, the metal powder and the oxide powder are both analytically pure powders, and the powders are sieved through a -100 mesh screen.

[0079] Specifically, in the above step 1, the temperature for the pretreatment of the metal powder drying is 85° C. and the time is 12 h; the temperature for the pretreatment of the oxide powder drying is 100° C. and the time is 16 h.

[0080] Specifically, in the above step 2, the mass ratio of the dispersant to the sum of the mass of the metal powder and the oxide powder is 3:5; the ball milling speed is 400 rpm, and the ball milling time is 12 h; after ball milling, a mixed powder with a size of less than 325 mesh can be obtained.

[0081] Specifically, in the above step 3, the slurry is transferred to a vacuum drying oven, preferably at a temperature of 85° C. and a drying time of 24 h. The vacuum degree should be maintained at less than -0.1 MPa before the temperature is raised.

[0082] Specifically, in the above step 4, the step of vacuum hot pressing sintering includes: placing the powder mold in a furnace, reducing the vacuum degree to less than 10 -2 After reaching Pa, the temperature began to rise to 600°C and was kept at this temperature for 0.5h; the temperature was continued to rise and pressurized to 1100°C, and the pressurization method was unidirectional pressurization to 25MPa, and the temperature was kept at this temperature for 2h. The temperature was lowered to room temperature at a rate of 5°C / min to demold and obtain a high metallic phase metal ceramic inert anode material.

[0083] The microstructure of the high metallic phase metal ceramic inert anode material of this embodiment is as follows: Figure 1 shown.

[0084] The size of the high metallic phase metal ceramic inert anode material of this embodiment is Φ50×35mm, and its density is 94.71%; the conductivity at room temperature is 12547.01S / cm; micro cracks can be observed after 15 thermal shock cycles, and obvious damage appears on the surface of the material after 68 thermal shock cycles, and the thermal shock resistance is good; 780℃ low temperature electrolysis (current density 0.45A / cm 2 ), the average working voltage is 3.32V and the equivalent annual corrosion rate is 0.475cm / a.

[0085] Example 2

[0086] The present embodiment provides a high metallic phase metal ceramic inert anode material, which is composed of a metal phase and a ceramic phase; in terms of mass fraction, the metal phase accounts for 75% of the high metallic phase metal ceramic inert anode material, and the rest is the ceramic phase; the metal phase contains Ni, Fe, and Cu, and in the metal phase, the mass fraction of Ni is 30%, the mass fraction of Fe is 38%, and the mass fraction of Cu is 32%, and the ceramic phase is NiFe2O4-based ceramic.

[0087] The preparation method of the high metallic phase metal ceramic inert anode material of this embodiment is substantially the same as that of embodiment 1, except that:

[0088] In step 1, the metal powder includes Ni powder, Fe powder and Cu powder, and the oxide powder includes NiO and Fe2O3; the mass ratio of the metal powder to the oxide powder is 75:25; in the metal powder, the mass fraction of Ni is 30%, the mass fraction of Fe is 38%, and the mass fraction of Cu is 32%; in the oxide powder, the mass fraction of NiO is 31.92%, and the mass fraction of Fe2O3 is 68.08%.

[0089] In step 1, the temperature for pre-drying the metal powder is 75° C. for 16 h; the temperature for pre-drying the oxide powder is 120° C. for 12 h.

[0090] In step 2, the mass ratio of the dispersant to the sum of the mass of the metal powder and the oxide powder is 3:5; the ball milling speed is 300 rpm, and the ball milling time is 18 h; after ball milling, a mixed powder with a size of less than 325 mesh can be obtained.

[0091] In step 4, the vacuum hot pressing sintering step includes: placing the powder mold in a furnace, reducing the vacuum degree to less than 10 -2 After reaching Pa, the temperature was started to rise to 580°C and kept at this temperature for 1 hour; the temperature was continued to rise and pressurized to 1100°C, and the pressurization method was unidirectional pressurization to 25MPa, and the temperature was kept at this temperature for 2 hours. The temperature was lowered to room temperature at a rate of 5°C / min, and the mold was demolded to obtain a high metallic phase metal ceramic inert anode material.

[0092] The size of the high metallic phase metal ceramic inert anode material of this embodiment is Φ50×35mm, and its density is 94.56%; the conductivity at room temperature is 14077.28S / cm; cracks can be observed after 15 thermal shock cycles, and obvious damage appears on the surface of the material after 69 thermal shock cycles, and the thermal shock resistance is good; 780℃ low temperature electrolysis (current density 0.45A / cm 2 ), the average working voltage is 3.28V and the equivalent annual corrosion rate is 0.531cm / a.

[0093] Example 3

[0094] The present embodiment provides a high metallic phase metal ceramic inert anode material, which is composed of a metal phase and a ceramic phase; in terms of mass fraction, the metal phase accounts for 75% of the high metallic phase metal ceramic inert anode material, and the rest is the ceramic phase; the metal phase contains Ni, Fe, and Cu, and in the metal phase, the mass fraction of Ni is 58%, the mass fraction of Fe is 37%, and the mass fraction of Cu is 5%, and the ceramic phase is NiFe2O4-based ceramic.

[0095] The preparation method of the high metallic phase metal ceramic inert anode material of this embodiment is substantially the same as that of embodiment 1, except that:

[0096] In step 1, the metal powder includes Ni powder, Fe powder and Cu powder, and the oxide powder includes NiO and Fe2O3; the mass ratio of the metal powder to the oxide powder is 75:25; in the metal powder, the mass fraction of Ni is 58%, the mass fraction of Fe is 37%, and the mass fraction of Cu is 5%; in the oxide powder, the mass fraction of NiO is 31.92%, and the mass fraction of Fe2O3 is 68.08%.

[0097] In step 1, the temperature for pre-drying the metal powder is 100° C. for 8 h; the temperature for pre-drying the oxide powder is 95° C. for 18 h.

[0098] In step 2, the mass ratio of the dispersant to the sum of the mass of the metal powder and the oxide powder is 3:5; the ball milling speed is 400 rpm, and the ball milling time is 12 h; after ball milling, a mixed powder with a size of less than 325 mesh can be obtained.

[0099] In step 4, the vacuum hot pressing sintering step includes: placing the powder mold in a furnace, reducing the vacuum degree to less than 10 -2 After reaching Pa, the temperature was started to rise to 550°C and kept at this temperature for 2h; the temperature was continued to rise and pressurized to 1100°C, and the pressurization method was unidirectional pressurization to 25MPa, and the temperature was kept at this temperature for 2h. The temperature was lowered to room temperature at a rate of 5°C / min to demold and obtain a high metallic phase metal ceramic inert anode material.

[0100] The size of the high metallic phase metal ceramic inert anode material of this embodiment is Φ50×35mm, and its density is 94.47%; the conductivity at room temperature is 10374.35S / cm; cracks can be observed after 14 thermal shock cycles, and the material is obviously damaged after 65 thermal shock cycles, and the thermal shock resistance is good; 780℃ low temperature electrolysis (current density 0.45A / cm 2 ), the average working voltage is 3.41V and the equivalent annual corrosion rate is 0.437cm / a.

[0101] Example 4

[0102] The present embodiment provides a high metallic phase metal ceramic inert anode material, which is composed of a metal phase and a ceramic phase; in terms of mass fraction, the metal phase accounts for 90% of the high metallic phase metal ceramic inert anode material, and the rest is the ceramic phase; the metal phase contains Ni, Fe, and Cu, and in the metal phase, the mass fraction of Ni is 43%, the mass fraction of Fe is 32%, and the mass fraction of Cu is 25%, and the ceramic phase is NiFe2O4-based ceramic.

[0103] The preparation method of the high metallic phase metal ceramic inert anode material of this embodiment is substantially the same as that of embodiment 1, except that:

[0104] In step 1, the metal powder includes Ni powder, Fe powder and Cu powder, and the oxide powder includes NiO and Fe2O3; the mass ratio of the metal powder to the oxide powder is 90:10; in the metal powder, the mass fraction of Ni is 43%, the mass fraction of Fe is 32%, and the mass fraction of Cu is 25%; in the oxide powder, the mass fraction of NiO is 31.92%, and the mass fraction of Fe2O3 is 68.08%.

[0105] In step 1, the temperature for pre-drying the metal powder is 95° C. for 9 hours; the temperature for pre-drying the oxide powder is 110° C. for 14 hours.

[0106] In step 2, the mass ratio of the dispersant to the sum of the mass of the metal powder and the oxide powder is 3:5; the ball milling speed is 300 r / min, and the ball milling time is 18 h; after ball milling, a mixed powder with a size of less than 325 mesh can be obtained.

[0107] In step 4, the vacuum hot pressing sintering step includes: placing the powder mold in a furnace, reducing the vacuum degree to less than 10 -2 After reaching Pa, the temperature began to rise to 560°C and was kept at this temperature for 1.5 hours; the temperature was continued to rise and pressurized to 1100°C, and the pressurization method was unidirectional pressurization to 25MPa, and the temperature was kept at this temperature for 2 hours. The temperature was lowered to room temperature at a rate of 7°C / min to demold and obtain a high metallic phase metal ceramic inert anode material.

[0108] The size of the high metallic phase metal ceramic inert anode material of this embodiment is 300×200×100 mm, and its density is 97.33%; its room temperature conductivity is 2.5×10 4 S / cm; micro cracks can be observed after 12 thermal shock cycles, and slight damage appears on the surface of the material after 72 thermal shock cycles, indicating good thermal shock resistance; 780℃ low temperature electrolysis (current density 0.45A / cm 2 ), the average working voltage is 3.16V and the equivalent annual corrosion rate is 1.45cm / a.

[0109] Example 5

[0110] The present embodiment provides a high metallic phase metal ceramic inert anode material, which is composed of a metal phase and a ceramic phase; in terms of mass fraction, the metal phase accounts for 51% of the high metallic phase metal ceramic inert anode material, and the rest is the ceramic phase; the metal phase contains Ni, Fe, and Cu, and in the metal phase, the mass fraction of Ni is 43%, the mass fraction of Fe is 32%, and the mass fraction of Cu is 25%, and the ceramic phase is NiFe2O4-based ceramic.

[0111] The preparation method of the high metallic phase metal ceramic inert anode material of this embodiment is substantially the same as that of embodiment 1, except that:

[0112] In step 1, the metal powder includes Ni powder, Fe powder and Cu powder, and the oxide powder includes NiO and Fe2O3; the mass ratio of the metal powder to the oxide powder is 51:49; in the metal powder, the mass fraction of Ni is 43%, the mass fraction of Fe is 32%, and the mass fraction of Cu is 25%; in the oxide powder, the mass fraction of NiO is 31.92%, and the mass fraction of Fe2O3 is 68.08%.

[0113] In step 4, the vacuum hot pressing sintering step includes: placing the powder mold in a furnace, reducing the vacuum degree to less than 10 -2 After Pa, the temperature began to rise to 600°C, and the temperature was kept for 0.5h and then the temperature was increased to 1100°C. The pressurization method was unidirectional pressurization to 30MPa, and the temperature was kept for 2h. The temperature was lowered to room temperature at a rate of 4°C / min to demold and obtain a high metallic phase metal ceramic inert anode material.

[0114] The size of the high metallic phase metal ceramic inert anode material of this embodiment is Φ30×25mm, and its density is 94.06%; the conductivity at room temperature is 3424.66S / cm; the number of thermal shock cycles is that after 9 cycles, tiny cracks can be observed, and after 31 thermal shock cycles, the material is obviously damaged; 780℃ low temperature electrolysis (current density 0.45A / cm 2 ), the average working voltage is 3.58V and the equivalent annual corrosion rate is 0.139cm / a.

[0115] Example 6

[0116] The present embodiment provides a high metallic phase metal ceramic inert anode material, which is composed of a metal phase and a ceramic phase; in terms of mass fraction, the metal phase accounts for 75% of the high metallic phase metal ceramic inert anode material, and the rest is a ceramic phase; the metal phase contains Ni, Fe, and Cu, and in the metal phase, the mass fraction of Ni is 43%, the mass fraction of Fe is 32%, and the mass fraction of Cu is 25%, and the ceramic phase is a NiFe2O4-based ceramic, and the ceramic phase also includes NiO.

[0117] The preparation method of the high metallic phase metal ceramic inert anode material of this embodiment is substantially the same as that of embodiment 1, except that:

[0118] In step 4, the vacuum hot pressing sintering step includes: placing the powder mold in a furnace, reducing the vacuum degree to less than 10 -2 After reaching Pa, the temperature was started to rise to 600°C and kept at this temperature for 1 hour; the temperature was continued to rise and pressurized to 1100°C, and the pressurization method was unidirectional pressurization to 35MPa, and the temperature was kept at this temperature for 2 hours. The temperature was lowered to room temperature at a rate of 5°C / min to demold and obtain a high metallic phase metal ceramic inert anode material.

[0119] The size of the high metallic phase metal ceramic inert anode material of this embodiment is Φ50×35mm, and its density is 96.36%; the conductivity at room temperature is 18036.67S / cm; cracks appear on the surface after 16 thermal shock cycles, and obvious damage appears on the surface of the material after 70 thermal shock cycles, and the thermal shock resistance is good; 780℃ low temperature electrolysis (current density 0.45A / cm 2), the average working voltage is 3.24V and the equivalent annual corrosion rate is 0.618cm / a.

[0120] The high metallic phase metal ceramic inert anode material of the present invention has high density, good electrical conductivity, thermal shock resistance, and corrosion resistance, for example, an equivalent annual corrosion rate of 1.45 cm / a or less, for example, 0.139 cm / a to 1.45 cm / a, and excellent machinability, and can be used for metal ceramic inert anodes. Thermal shock resistance: Example 4> Example 6, Example 2, Example 1, Example 3> Example 5. The thermal shock resistance of the high metallic phase metal ceramic inert anode material of Example 6, Example 2, Example 1, and Example 3 is equivalent.

[0121] The inventor has conducted a large number of experimental studies during the research process, and now uses some solutions with poor performance as comparative examples.

[0122] Comparative Example 1

[0123] The present comparative example provides a low metallic phase metal ceramic inert anode material, which is composed of a metal phase and a ceramic phase; in terms of mass fraction, the metal phase accounts for 5% of the low metallic phase metal ceramic inert anode material, and the rest is the ceramic phase; the metal phase contains Ni, Fe, and Cu, and in the metal phase, the mass fraction of Ni is 43%, the mass fraction of Fe is 32%, and the mass fraction of Cu is 25%, and the ceramic phase is a NiFe2O4-based ceramic.

[0124] The preparation method of this comparative example is the same as that of Example 1 and will not be repeated here.

[0125] The density of the low-metal phase metal ceramic inert anode material in this comparative example is 85.67%; the conductivity at room temperature is 0.8749S / cm; the material is extremely brittle, and the sample with a size of Φ25mm×10mm shatters during demolding. This material has great size restrictions and the molding effect is far worse than that of Example 1.

[0126] Comparative Example 2

[0127] The present comparative example provides a high metallic phase metal ceramic inert anode material, which is composed of a metal phase and a ceramic phase; in terms of mass fraction, the metal phase accounts for 75% of the high metallic phase metal ceramic inert anode material, and the rest is a ceramic phase; the metal phase contains Ni, Fe, and Cu, and in the metal phase, the mass fraction of Ni is 43%, the mass fraction of Fe is 32%, and the mass fraction of Cu is 25%, and the ceramic phase is a NiFe2O4-based ceramic.

[0128] The difference between the preparation method of this comparative example and that of Example 1 is that the vacuum degree is reduced to less than 10 -2After reaching Pa, the temperature and pressure were directly increased to 950°C and kept at this temperature and pressure for 2h.

[0129] The density of the high metal phase metal ceramic inert anode material in this comparative example is 81.33%; the material is not dense enough due to the large number of pores, the size is Φ35mm×25mm, the processing effect is not good, there are many slags, and the equivalent annual corrosion rate is about 2.201cm / a. The sintering temperature of this comparative example is low, and there is no insulation process, the material density is not good, and the corrosion resistance is poor.

[0130] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A high metallic phase metal ceramic inert anode material, characterized in that: The high metallic phase metal ceramic inert anode material is composed of a metallic phase and a ceramic phase; in terms of mass fraction, the metallic phase accounts for 51% to 99% of the high metallic phase metal ceramic inert anode material, and the rest is a ceramic phase; the metallic phase contains Ni, Fe, and Cu, and the mass fraction of Ni in the metallic phase is 30% to 60%.

2. The high metallic phase cermet inert anode material according to claim 1, characterized in that: The ceramic phase is NiFe2O4-based ceramic.

3. The high metallic phase cermet inert anode material according to claim 1, characterized in that: In the metal phase, the molar ratio of Ni to Fe is 1.5:2 to 3:

2.

4. The high metallic phase cermet inert anode material according to claim 2, characterized in that: The ceramic phase also includes NiO.

5. A method for preparing a high metallic phase metal ceramic inert anode material according to any one of claims 1 to 4, characterized in that: The steps include: Step 1, pre-drying the metal powder and the oxide powder respectively; Step 2, mixing the metal powder and the oxide powder after drying and pretreatment, adding a dispersant, and ball milling to obtain a slurry; Step 3, drying the slurry; Step 4: vacuum hot-press sintering the dried powder to obtain a high-metal phase metal ceramic inert anode material.

6. The preparation method according to claim 5, characterized in that: In step 1, the metal powder includes Ni powder, Fe powder and Cu powder, and the oxide powder includes NiO and Fe2O3.

7. The preparation method according to claim 5, characterized in that: In the step 2, the dispersant is anhydrous ethanol.

8. The preparation method according to claim 5, characterized in that: In the step 2, the mass ratio of the dispersant to the sum of the mass of the metal powder and the oxide powder is 2 to 4:

5.

9. The preparation method according to claim 5, characterized in that: In step 3, the drying temperature is 85-110°C.

10. Application of a high metallic phase metal ceramic inert anode material, characterized in that: The high metallic phase metal ceramic inert anode material described in any one of claims 1 to 4 or the high metallic phase metal ceramic inert anode material prepared by the preparation method described in any one of claims 5 to 9 can be used for inert anodes.